Cyber security for educational leaders : a guide to understanding and implementing technology policies - Sianjina, Rayton R.; Phillips, Richard, 1958- (New York : Routledge, 2013)
"As leaders are increasingly implementing technologies into their districts and schools, they need to understand the implications and risks of doing so. Cyber Security for Educational Leaders is a much-needed text on developing, integrating, and understanding technology policies that govern schools and districts. Based on research and best practices, this book discusses the threats associated with technology use and policies and arms aspiring and practicing leaders with the necessary tools to protect their schools and to avoid litigation.Special Features:A Cyber Risk Assessment Checklist and Questionnaire helps leaders measure levels of risk in eight vital areas of technology usage. Case vignettes illuminate issues real leaders have encountered and end-of-chapter questions and activities help readers make connections to their own practice.Chapter alignment with the ELCC standards.An entire chapter on Copyright and Fair Use that prepares leaders for today's online world.A Companion Website with additional activities, assessment rubrics, learning objectives, and PowerPoint slides. "--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Educational technology -- Security measures; Cyberspace -- Security measures; Computer security; Electronic books